(untitled) (Dhaka Shishu (Children) Hospital Journal, 2024)
Background: In Bangladesh, the re-emergence of dengue patients has created a huge burden on our children’s morbidity and mortality. A dengue outbreak erupted in Bangladesh in 2019, resulting in the highest number of deaths to date. Objective: To see the clinical and laboratory profile and hospital outcome of the children admitted in Bangladesh Shishu Hospital & Institute. Methods: A prospective observational study was conducted among the children having dengue infection at the inpatient department of Bangladesh Shishu Hospital & Institute from 1st August 2022 to 31st January 2023. A total of 385 confirmed dengue cases were finally enrolled. Data collected from a standard questionnaire were analysed using SPSS 26.0 statistical software. Results: Mean age of the dengue patients were 6.09(±4.74) years. Most of the patients suffering from dengue were male 227(59%). According to their BMI, underweight 254(66%), normal weight 97(25.2%), overweight 24(6.2%) and obese 10(2.6%). Most underweight patients age group were 1-5 years age 106(75.7%), according to the association of BMI with age considering p value 0.058. A diagnostic confirmation test revealed that 296 patients (76.9%) were NS1 positive, 65(16.9%) were IgM positive, 21(5.5%) were IgG positive, NS1 & IgM both positive 2(0.5%) and NS1 & IgG positive 1(0.3%). Most of the respondents according to their symptoms had fever 383(99.5%), less urine output 359(93.2%), anorexia 225(58.4%), abdominal pain 136(35.3%), nausea/ vomits 126(32.7%), headache 94(24.4%), cough 86(22.3%), joint pain 54(14.0%), rash 44(11.4%), retro orbital pain 34(8.8%), diarrhoea 31(8.1%), back pain 30(7.8%), chill 26(6.8%), others 33(8.6%), etc. Respondents according to sign had enlarged lymph node 40(10.4%), dehydration 9(2.3%), enlarged liver 10(2.6%), ascites 4(1.0%), joint swelling 1(0.3%) and splenomegaly 1(0.3%). Most of the respondents according to the final diagnosis had dengue fever 157(40.8%), dengue fever with warning sign 200(51.9%) and severe dengue 28(7.3%), among them dengue shock syndrome 16(4.2%), expanded dengue syndrome 9(2.3%) and dengue hemorrhagic fever 3(0.8%). Conclusion: To reduce mortality and morbidity, health care providers must remain alert of the changing pattern of presentation. This challenge requires proper public health interventions to reduce the morbidity and mortality due to severe dengue infection. The outcomes of this study will help to identify potential areas for improvement. DS (Child) H J 2023; 39(1): 9-17